2013
DOI: 10.1111/his.12156
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐17‐producing cell infiltration in the breast cancer tumour microenvironment is a poor prognostic factor

Abstract: Our results indicate that a high level of IL-17-producing cells in the breast cancer tumour microenvironment is a poor prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
93
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 44 publications
19
93
0
2
Order By: Relevance
“…Tumor infiltration by IL-17-producing cells has been proposed to be a negative prognostic factor, 19 suggesting that Th17 cells may be detrimental in this context. However, the underlying biological mechanisms have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor infiltration by IL-17-producing cells has been proposed to be a negative prognostic factor, 19 suggesting that Th17 cells may be detrimental in this context. However, the underlying biological mechanisms have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…tumors, these cells are indicative of a poor prognosis for the patient (9,11,12). TGF-α is secreted by various types of cells and stimulates their proliferation, differentiation and development (10).…”
Section: Association Of Serum Interleukin-10 Interleukin-17amentioning
confidence: 99%
“…29 Another study reported that post-chemotherapy samples were used when no pretreatment samples were available for immunohistochemistry. 30 A final potential risk factor was observed in a study of leukemia patients treated with allogeneic stem cell transplantation after myeloablative conditioning, which included donors that varied from related to unrelated and different prophylaxis regimens to prevent graft-vs.-host disease. 31 Additional study details and concerns are listed per sample type in Tables S1-4.…”
Section: Study Design and Selection Criteriamentioning
confidence: 99%